2014
DOI: 10.1371/journal.pone.0109981
|View full text |Cite
|
Sign up to set email alerts
|

The Telomerase Reverse Transcriptase Subunit from the Dimorphic Fungus Ustilago maydis

Abstract: In this study, we investigated the reverse transcriptase subunit of telomerase in the dimorphic fungus Ustilago maydis. This protein (Trt1) contains 1371 amino acids and all of the characteristic TERT motifs. Mutants created by disrupting trt1 had senescent traits, such as delayed growth, low replicative potential, and reduced survival, that were reminiscent of the traits observed in est2 budding yeast mutants. Telomerase activity was observed in wild-type fungus sporidia but not those of the disruption mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 55 publications
(60 reference statements)
1
21
0
Order By: Relevance
“…maydis trt1 deletion causes progressive telomere loss and the emergence of type I-like survivors Because we are interested in understanding the roles of repair proteins in both telomerase-positive and telomerasenegative cells, we first characterized the U. maydis telomerase-null mutant. Bautista-Espana et al recently reported the identification of U. maydis Trt1 (the catalytic subunit of telomerase), and demonstrated telomere loss and the emergence of survivors in the trt1D mutants (Bautista-Espana et al, 2014). Notably, most of the TRF (telomere restriction fragment) analysis in this study was conducted using a sub-telomeric probe, making it difficult to compare the findings to typical assays that employ the telomere repeat probe.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…maydis trt1 deletion causes progressive telomere loss and the emergence of type I-like survivors Because we are interested in understanding the roles of repair proteins in both telomerase-positive and telomerasenegative cells, we first characterized the U. maydis telomerase-null mutant. Bautista-Espana et al recently reported the identification of U. maydis Trt1 (the catalytic subunit of telomerase), and demonstrated telomere loss and the emergence of survivors in the trt1D mutants (Bautista-Espana et al, 2014). Notably, most of the TRF (telomere restriction fragment) analysis in this study was conducted using a sub-telomeric probe, making it difficult to compare the findings to typical assays that employ the telomere repeat probe.…”
Section: Resultsmentioning
confidence: 80%
“…Bautista‐Espana et al . recently reported the identification of U. maydis Trt1 (the catalytic subunit of telomerase), and demonstrated telomere loss and the emergence of survivors in the trt1Δ mutants (Bautista‐Espana et al ., ). Notably, most of the TRF (telomere restriction fragment) analysis in this study was conducted using a sub‐telomeric probe, making it difficult to compare the findings to typical assays that employ the telomere repeat probe.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…maydis ku mutants, we analyzed several independent trt1 ku70 nar1 double mutants, which were constructed by first deleting the trt1 gene (encoding the telomerase reverse transcriptase in U . maydis [ 28 ]) and then introducing the ku70 nar1 allele. Similar to the ku70 nar1 single mutant, the double mutant experienced growth arrest when switched to the restrictive condition for ku70 expression ( Fig 3A and 3B ), and exhibited profound telomere aberrations ( Fig 3C, 3D and 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, unlike budding yeast but similar to fission yeast, U. maydis has a mammal-like telomere nucleoprotein complex (Yu, et al 2013). Notably, initial analysis of the U. maydis telomerase-null mutant trt1 Δ did not reveal an ALT-like pathway, but rather survivors that resemble the S. cerevisiae type I survivors ((Bautista-Espana, et al 2014) and E.Y.Y., unpublished data). Instead, the Ustilago ALT-like pathway was discovered in the course of investigating Ku function.…”
Section: A Ustilago Maydis Model Of the Alt Pathwaymentioning
confidence: 99%